Lamna nasus - Mollen, Frederik H.; Wintner, Sabine P.; Iglésias, Samuel P.; Van, Sean R.; Jagt, John W. M. (Zenodo, 2012)
Lamna nasus Fresh material : 3 specimens, ERB 0 928, male, 1620 mm TL, 21 September 2007, La Rochelle fish market, France, northeast Atlantic Ocean; ERB 0 929, male, 1740 mm TL, same date and provenance; ERB 0 930, male, 1660 mm TL, same date and provenance. Additional material : 5 dried chondrocrania, IRScNB 476 and IRScNB 2189β, juvenile specimens, sex, no data; IRScNB 1352β, subadult specimen, male, length unknown, Belgium, North Sea; IRScNB 1353, adult specimen, no data; IRScNB 2189, juvenile specimen, no data, Nice, France, Mediterranean. Additional illustrations : Parker (1887, pl. 4, figs. 2, 4; pl. 5, unnumbered fig. (lower part of plate only), Garman (1913, pl. 62, figs. 1–3); Block & Carey (1985, fig. 4A–B), Chevrier (1986, p. 6, unnumbered figs.), Compagno (1990, figs. 5N, 6M, 7N; non fig. 6N, mislabelled), Goto (1996, fig. 5D), Wilga (2005, fig. 3C), and Mollen (2010, fig. 4A–B; pls 1–3). Published as part of Mollen, Frederik H., Wintner, Sabine P., Iglésias, Samuel P., Van, Sean R. & Jagt, John W. M., 2012, Comparative morphology of rostral cartilages in extant mackerel sharks (Chondrichthyes, Lamniformes, Lamnidae) using CT scanning, pp. 29-43 in Zootaxa 3340 on page 32, DOI: 10.5281/zenodo.215285